The first five terms of the sequence are:
a1 = 1 + 9 = 10
a2 = 2 + 9 = 11
a3 = 3 + 9 = 12
a4 = 4 + 9 = 13
a5 = 5 + 9 = 14
Find the first five terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = n + 9
first 5 terms
7 answers
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = 4(2)n
frist four terms
an = 4(2)n
frist four terms
The first four terms of the sequence are:
a1 = 4(2)^1 = 4(2) = 8
a2 = 4(2)^2 = 4(4) = 16
a3 = 4(2)^3 = 4(8) = 32
a4 = 4(2)^4 = 4(16) = 64
a1 = 4(2)^1 = 4(2) = 8
a2 = 4(2)^2 = 4(4) = 16
a3 = 4(2)^3 = 4(8) = 32
a4 = 4(2)^4 = 4(16) = 64
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = –9n
first four terms
an = –9n
first four terms
The first four terms of the sequence are:
a1 = -9(1) = -9
a2 = -9(2) = -18
a3 = -9(3) = -27
a4 = -9(4) = -36
a1 = -9(1) = -9
a2 = -9(2) = -18
a3 = -9(3) = -27
a4 = -9(4) = -36
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = –9n
frist four terms
an = –9n
frist four terms
The first four terms of the sequence are:
a1 = -9(1) = -9
a2 = -9(2) = -18
a3 = -9(3) = -27
a4 = -9(4) = -36
a1 = -9(1) = -9
a2 = -9(2) = -18
a3 = -9(3) = -27
a4 = -9(4) = -36